EXPERIMENTAL DETERMINATION OF THE DIFFUSION COEFFICIENT FOR CALCIUM IN OLIVINE BETWEEN 900°C AND 1500°C - Coogan L.A.; Hain A.; Stahl S.; Chakraborty S. (My University, 2005)
Experiments have been carried out to determine the temperature, oxygen fugacity (fO2) and compositional dependence of the tracer diffusion coefficient (D) of calcium in olivine. These data constrain the diffusion coefficient over the temperature range 900 to 1500°C for the three principal crystallographic axes. Well constrained linear relationships between the reciprocal of the absolute temperature and log(D) exist at any given oxygen fugacity. There is a strong dependence of the diffusion coefficient on oxygen fugacity with D ~ fO2(1/3). This makes a knowledge of the T-fO2 path followed by geological samples a prerequisite for modelling Ca diffusion in olivine. The best fitting preexponential factor (Do) and activation energy (E) to the Arrhenius equation log (D) = log [Do exp(−E/RT)] + 0.31Δ log fO2 for Ca diffusion in olivine at a given oxygen fugacity (fO2*) are given by:diffusion along [100]: log [Do (m2/s)] = −10.78 ± 0.43; E = 193 ± 11 kJ/moldiffusion along [010]: log [Do (m2/s)] = −10.46 ± 0.37; E = 201 ± 10 kJ/moldiffusion along [001]: log [Do (m2/s)] = −10.02 ± 0.29; E = 207 ± 8 kJ/molwhere Δ log fO2 = log[fO2*] − log[10−12] with fO2* in units of bars. There is no measurable compositional dependence of the diffusion coefficient between Fo83 and Fo92. Diffusion in Fo100 has a much higher activation energy than in Fe-bearing olivine and has a weaker fO2 dependence.